Where Sustainable School Meets the ‘Tthird Teacher’: Primary School Case Study From Barcelona, Spain - Brkovic, Marta; Pons, Oriol; Parnell, Rosie (ArchNet-IJAR, 2015)
Participatory evaluation of aspiring sustainable schools and their pedagogical potential has recently come into focus. A few authors have made a significant start in examining schools as both environmentally and socially sustainable environments, which might simultaneously represent the ‘third teacher’. However, discussion around this idea is new in Spain. This paper describes a participatory post-occupancy study conducted with teachers and pupils in Fort Pienc School, Barcelona, Spain. Findings reveal the pedagogical potential of the school’s spaces and fabric, characterised as ‘sustainable’, and highlight the aspects that the research participants feel are performing and underperforming. The paper concludes that if we want sustainable schools to be a strategy for renovating the educational process and for leading us towards a better tomorrow globally and locally,  new models for exploring the pedagogical potential of sustainable schools should be developed and the efforts of all relevant parties synchronised; from architects to governments, from pupils to teachers.